Anti-Adhesive Effect of Porous Polylactide Film in Rats - Chung, Kyu Jin (Polymers (Basel), 2021)
Excessive adhesion between tissues on a significant area can cause the development of disorders, cosmetic problems, and ileus. Methods for preventing adhesion include the use of drugs and anti-adhesion barriers for physical blocking. In this study, the adhesion prevention effect of polylactide film in porous form was analyzed. A porous polylactide film was manufactured using a molecular weight of at least 100,000. To generate porosity, 98% methylene chloride and 95% ethyl alcohol were used as solvents. The thickness, surface, and internal pore shape of film were investigated. The crystal structures and melting temperature of film were measured. In the rat model, the presence and severity of adhesion were then analyzed. The thickness of the film ranged from 10 to 20 µm. The surface of the film contained pores with diameters of less than 10 µm. Partial crystallinity appeared from 15° to 20°, but the structure was amorphous overall. In the rat cecum abrasion model, adhesion occurred in 3 of the 13 rats in the polylactide experimental group, representing a 23.1% incidence rate. There were statistically significant differences in the severity of adhesion. The use of porous polylactide films can reduce the incidence of adhesion.